Effect of Nasal Corticosteroid on Secretory Immunoglobulin A Measured in Rat Nasal Lavage: Experimental Study - AKSOY, Fadlullah; AKSOY, FADLULLAH; Dogan, REMZİ; DOĞAN, REMZI; Kocak, Ilker; VEYSELLER, Bayram; Ozturan, ORHAN; ÖZTURAN, ORHAN; Incir, Said (My University, 2015)
Objective In this study, we aimed to experimentally investigate the effects of nasal corticosteroids on the levels of secretory immunoglobulin A (sIgA) in nasal mucosa in rats.
Keywords: Mometasone furoate; nasal lavage; rat; secretory immunoglobulin A